2019
DOI: 10.37706/ijaz.v4i2.180
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Zakat Distribution as a Reduction In Poverty Case Study in the Province of West Sumatra

Abstract: West Sumatra Province has a high Muslim population and also has a high amount of zakat funds even though it is not yet potential. Regulation of zakat which is different from other provinces in West Sumatra is the existence of compulsory zakat regulations which are directly deducted from salaries for the State Civil Apparatus (ASN). This has a positive impact on the collection of zakat funds in West Sumatra. This should be accompanied by the application of good zakat to reduce poverty. This study used questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Thus, such empowerment is based on the investment and not in the form of consumption. Moreover, Sari et al (2019) suggest that the business empowerment conducted by BAZNAS should also be developed based on the priority scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, such empowerment is based on the investment and not in the form of consumption. Moreover, Sari et al (2019) suggest that the business empowerment conducted by BAZNAS should also be developed based on the priority scale.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Wibisono et al (2019) also narrate that the Zakat has a significant positive effect on increasing regional income and community benefit. Sari et al (2019) find that assuming economic growth of 6% West Sumatra Province will require six years to decrease the poverty rate; however, by using the Zakat as one of the poverty instruments managed professionally it can reduce poverty in 2.8 years. Moreover, with the assumption that economic growth is 7%, poverty alleviation can be achieved in 5.2 and 2.4 years with the contribution of Zakat.…”
Section: The Role Of Zakat As An Instrument Of Poverty Reduction In I...mentioning
confidence: 99%
“…Zakat is defined as alms or charity (Lewis, 2001;Tuan Ibrahim et al, 2020;Al-Malkawi & Javaid, 2017) Zakat has been tested in empirical studies and found to have a significant impact on the society and economy. Many empirical studies have investigated the impact of Zakat on poverty, such as in Malaysia (Senadjki & Sulaiman, 2015), in Indonesia (Herianigrum et al, 2020;Sari et al, 2019); and in Bangladesh (Ali et al, 2019). These scholars have found the benefit of zakat in reducing poverty in their countries.…”
Section: Performancementioning
confidence: 99%
“…Corporations are increasingly recognizing that digital accounting systems not only streamline financial processes but also have the potential to enhance sustainability reporting and practices (Alflaieh, 2022). Simultaneously, the Islamic tradition of zakat, which mandates the provision of alms to support the less fortunate, has found its place in the digital realm (Sari et al, 2019). Digital zakat platforms and technologies have emerged, offering individuals and corporations streamlined methods to fulfill their philanthropic obligations (Al-Zaqeba and Al-Rashdan, 2020).…”
Section: Introductionmentioning
confidence: 99%